Rethinking the Importance of the Individual within a Community of Data. Issue 4 (7th July 2020) - Spector‐Bagdady, Kayte; Beever, Jonathan
Abstract: The Covid‐19 crisis has underscored the importance of the collection and analysis of clinical and research data and specimens for ongoing work. The federal government recently completed a related revision of the human subjects research regulations, founded in the traditional principles of research ethics, but in this commentary, we argue that the analysis underpinning this revision overemphasized the importance of informed consent, given the low risks of secondary research. Governing the interests of a community is different from governing the interests of individuals, and here we suggest that, moving forward, the analyses of the risks of secondary research protocols be assessed from the perspective of the former .